The relationship between dividend policy and firm performance / Noor Qharmielah Khamis - Khamis, Noor Qharmielah (2015)
Dividend policy and firm performance is always being a debatable subject among the researcher especially on the dividend payout. Based on the previous studies, some researcher agrees with relationship between dividend policy and firm performance but there is some researchers also argue with this statement. So, this study is intended to investigate the relationship between dividend policy and firm performance among the Public listed companies in Bursa Malaysia during the period 2009 until 2013 which consists of various industries such as trading and services, industrial products, consumer product and property. The objective of the study is to identify the relationship between dividend policy, financial leverage and firm size towards firm performance. The investigation has been performed using cross sectional analysis. The finding of the study show there is a positive and negative relationship between dividend policy, financial leverage and firm size towards the firm performance. However, the result shows an insignifant relationship between the dependent and independent variables because of the weaknesses of cross sectional analysis and availability of data from Bursa Malaysia.